Integrated MRP and Wagner-Whitin Planning for Vehicle Cargo-Body Materials - Adelia Natalia Khundari; Asep Hermawan; Yayan Heru Haerudin (Global Writing Academica Researching and Publishing, 2026)
PT. XYZ is a vehicle-body manufacturer producing four cargo-body variants and experiencing a persistent mismatch between growing demand and material readiness. This study develops an integrated material-planning framework that combines trend forecasting, production planning, a Master Production Schedule (MPS), Material Requirements Planning (MRP), and a cost comparison between Lot for Lot (LFL) and the Wagner–Whitin algorithm. The dataset covers monthly sales and production from January 2024 to December 2025, bills of material, beginning inventory, supplier lead times, and company-provided inventory-cost parameters. Holt’s double exponential smoothing with α=0.3 and β=0.2 achieved a mean absolute percentage error of 2.50%, a mean absolute deviation of 0.737 units, and a mean squared error of 0.902. The 2026 demand forecast totaled 680 units and was consistently disaggregated among the four product variants. MRP generated time-phased gross requirements, net requirements, planned-order receipts, and planned-order releases. Under the company’s cost-accounting scope, Wagner–Whitin reduced total cost from IDR 330.40 million to IDR 271.29 million, saving IDR 59.11 million (17.89%). When the invariant finished-product component was excluded, the lot-sizing-sensitive cost decreased by 67.53%. The results indicate that combining MRP with dynamic lot sizing can improve material-timing reliability and inventory-cost efficiency, particularly for stable-demand items with relatively high ordering costs.